Evaluasi Pengalaman Penggunaan Aplikasi Posaja Menggunakan Metode UX Honeycomb - Setyaningrum, Diah Ayu; Harsadi, Paulus (Jurnal Ilmiah SINUS, 2025)
PT Pos Indonesia is one of the state-owned companies in Indonesia engaged in postal and logistics services. Pos Indonesia launched a new innovation by creating the PosAja application which aims to facilitate customers in sending packages and letters. However, there are features of PosAja that need to be improved based on the results of reviews from users, including a lack of understanding of the features of the PosAja application, users find it difficult to track the position of goods and the delivery flow is not clear or the position of the goods is not mentioned. Therefore, it is necessary to evaluate the PosAja application so that it can be even better in its future services.  This research uses the UX Honeycomb method to improve user experience in a digital product or service. The system design uses the Unified Modeling Language and is implemented using the PHP programming language and MySQL database. The results of the user experience evaluation of the PosAja application with the UX Honeycomb method show that the average value of variables that can be accessed is 3.57, can be found by 3.93, can be used by 3.76, useful by 4.05, valuable by 3.95, desirable by 4.19, and credible. by 3.82 which means that the value is included in the good category. Desirable, useful and valuable variables have a high average value which indicates that this application is needed by users and the variable accessed has the lowest average which indicates that this application needs improvement and improvement in terms of access speed. The results of the above research can provide recommendations to PT. POS to increase access speed so that users find it easier to use the application even though it is through cellphone media with insufficient signal due to geographical factors of users.